Finlay donovan is killing it ebook A novel. - Cosimano, Elle (Finlay Donovan, 2021)
"Getting the job done" for one single mom takes on a whole new meaning in Finlay Donovan is Killing It. A USA Today bestseller! One of Suspense Magazine 's "Best Thrillers of 2021" One of New York Public Library's Best Books of 2021 Nominated for the Left Coast Crime 2022 Lefty Award for the Best Humorous Mystery "Finlay Donovan is irresistible!"—Janet Evanovich Finlay Donovan is killing it . . . except, she's really not. She's a stressed-out single-mom of two and struggling novelist, Finlay's life is in chaos: the new book she promised her literary agent isn't written, her ex-husband fired the nanny without telling her, and this morning she had to send her four-year-old to school with hair duct-taped to her head after an incident with scissors. When Finlay is overheard discussing the plot of her new suspense novel with her agent over lunch, she's mistaken for a contract killer, and inadvertently accepts an offer to dispose of a problem husband in order to make ends meet . . . Soon, Finlay discovers that crime in real life is a lot more difficult than its fictional counterpart, as she becomes tangled in a real-life murder investigation. Fast-paced, deliciously witty, and wholeheartedly authentic in depicting the frustrations and triumphs of motherhood in all its messiness, hilarity, and heartfelt moments, Finlay Donovan Is Killing It is the first in a brilliant new series from YA Edgar Award nominee Elle Cosimano.